Entry and sequential distribution of an aquatic birnavirus in turbot (Scophthalmus maximus) - Novoa, Beatriz; Barja, J. L.; Figueras Huerta, Antonio (Aquaculture, 1995)
9 páginas, 4 figuras Experimental infections with a bimavims strain isolated from turbot (Scophthalmus maximus) were conducted by immersion and intraperitoneal injection in turbot. Virus could be recovered in skin, mucus and intestine from fish infected by immersion, only up to 3 days post-infection. The distribution in internal organs was fast after intraperitoneal injection and virus was recovered with high titres from intestine, kidney, liver and spleen. The lowest titres were detected in brain and gills. Virus was isolated from plasma and blood fractions of the intraperitoneally infected turbot. Preliminary work on the influence on infection of turbot by intraperitoneal injection on the haematological parameters shows that there is no significant difference between infected and uninfected fish in the haematocrit value, number of leukocytes and concentration of plasma proteins. This work was supported by Grant AGF93-0769-C02-02 from the Comisidn Interministerial de Ciencia y Tecnologia (CICYT). Peer reviewed